THIS ANSWER IS FOR f(3):
f(x)=x+3
f(3)=3+3
f(3)=6
THIS ANSWER IS FOR f(-2):
f(x)=x+3
f(-2)=-2+3
f(-2)=1
−3x + 6 = 5 | -6 (first step is: "subtract 6 from both sides" <span>)
</span>
-3x = 5-6
-3x = -1 | /(-3) (second step is: "<span>divide by (-3) on both sides</span>" <span>)
</span>
<span>
</span>
Answer:
x=53/9
Step-by-step explanation:
(x-2):5=7:9
9x-18=35
9x=35+18
9x=53
x=53/9
Answer:
Step-by-step explanation:
Answer:
$24,498,509.74
Step-by-step explanation:
The formula for the value as a function of time is ...
V(t) = P·e^(rt)
Filling in the numbers and doing the arithmetic, we have ...
V(35) = 3,000,000·e^(0.06·35) ≈ 24,498,509.74
Compounded continuously for 35 years, the investment will be worth $24,498,509.74.